'Can you wash off the hogwash?' – semantic transparency of first and second constituents in the processing of German compounds. Issue 4 (21st April 2017) - Smolka, Eva; Libben, Gary
ABSTRACT: This study examined whether the lexical processing of German compounds is driven by semantic transparency and applied an overt visual priming experiment to manipulate the transparency of modifiers or heads. When manipulating modifiers, participants responded to compounds like Hundeauge ("dog's eye") or Hühnerauge ("corn"; literal: "hen's eye") that were preceded by their transparent ( Hund, "dog") or opaque ( Huhn, "hen") modifier, respectively, or unrelated controls. When manipulating heads, participants responded to compounds like Pferdeohr ("horse's ear") or Eselsohr ("dog-ear"; literal: "donkey's ear") that were preceded by their transparently or opaquely related head Ohr ("ear"), or an unrelated control. Results showed that compound frequency was facilitatory, head frequency was inhibitory, and modifier frequency was both. These findings indicate that compound constituents and their corresponding independent words compete in compound processing. Furthermore, both modifiers and heads induced priming regardless of their semantic transparency, indicating that lexical representation in German incorporates constituent structure, regardless of semantic transparency.